Diseño de una rutaturistica para promocionar los atractivos turísticos del cantón La Mana, año 2021 - Bonilla Intriago, Ricardo Adalberto (2021)
The present research work consists of designing a tourist route to promote the tourist attractions of the Canton La Mana, located in the province of Cotopaxi, whose main objective is to promote our city with quality and that it diversifies through the resources or natural tourist attractions that we have. The research was developed with an analytical and descriptive character. This research work began with the development of the theoretical foundation, for which a search of the variables was carried out in the different available sources, to achieve the correct definition and from there begin with the development of the case. Chapter one points out the proposal of a tourism promotion strategy that allows to improve the influx of visitors in the Canton, which will contribute to solving the problems, through applicable strategies, reaching the interest of national and local tourists. Chapter two contains the situations detected where the tourist places of the city and the attractions of each one are detailed, in the proposed solutions a guide with clear information for tourists was presented, in addition to the conclusions and recommendations relevant to the investigation. The purpose of this project is that the tourist promotion is a contribution to the tourism of the Canton La Mana, because by promoting the sites that the Canton has in an appropriate way, with a well-directed promotion through different means such as posters, volantes, or social networks, among others, focused on achieving the increase in the influx of visitors being the population the main beneficiary through the economic resources that are obtained from tourist activity.